Multimodal Interactive Pattern Recognition and Applications - Toselli, Alejandro Héctor; Vidal, Enrique; Casacuberta, Francisco (Springer London : Imprint: Springer, 2011)
Many real-world applications of pattern recognition (PR) systems require human post-processing to correct the errors committed by machines. This can create bottlenecks in recognition systems, yielding high operational costs. This important text/reference proposes a radically different approach to this problem, in which users of a system are involved during the recognition process. This can help to avoid later errors and reduce the costs associated with post-processing. The book also examines a range of advanced multimodal interactions between the machine and the users, including handwriting, speech and gestures. Topics and features: Presents a thorough introduction to the fundamental concepts and general PR approaches for multimodal interaction modelling and search (or inference) Provides numerous examples and a helpful Glossary Includes work carried out in the context of the Spanish research program Multimodal Interaction in Pattern Recognition and Computer Vision (MIPRCV), which involves more than 100 highly-qualified researchers from ten research institutions Discusses approaches for computer-assisted transcription of handwritten and spoken documents Examines systems for computer-assisted language translation, interactive text generation and parsing, relevance-based image retrieval, and interactive document layout analysis Reviews several full working prototypes of multimodal interactive PR applications, including live demonstrations that can be publicly accessed through the Internet Addressing the emerging field of interactive and multimodal systems in a fresh, unified and integrated way, this unique book is highly recommended reading for graduate students, academic and industrial researchers, lecturers, and practitioners working in the field of pattern recognition. Dr. Alejandro Héctor Toselli is an Associate Professor at the Department of Computer Systems and Computation of the Polytechnic University of Valencia, Spain. Dr. Enrique Vidal and Dr. Francisco Casacuberta both hold the title of Full Professor at the same institution.